2000
DOI: 10.1097/00003246-200012000-00029
|View full text |Cite
|
Sign up to set email alerts
|

Moderate hypothermia improves imbalances of thromboxane A2 and prostaglandin I2 production after traumatic brain injury in humans

Abstract: The current results from a limited number of patients suggest that moderate hypothermia may reduce prostanoid production after TBI, thereby attenuating an imbalance of thromboxane A2 and prostaglandin I2. However, it must be clarified whether the changes in the prostanoid after moderate hypothermia are a secondary effect of other mediator changes or whether they simply represent an epiphenomenon that is mechanistically unrelated to damage in TBI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
1
4

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(50 citation statements)
references
References 25 publications
1
44
1
4
Order By: Relevance
“…The 2 papers for which there was disagreement were considered for exclusion because some of the patients were pediatric. 27,34 As these studies reported individual patient data, we were able to exclude the pediatric data and we included only the adult data in our final analysis. During a later stage of analysis it was discovered that both of these studies were reporting the same set of patient results; therefore, only the most recent one was included.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The 2 papers for which there was disagreement were considered for exclusion because some of the patients were pediatric. 27,34 As these studies reported individual patient data, we were able to exclude the pediatric data and we included only the adult data in our final analysis. During a later stage of analysis it was discovered that both of these studies were reporting the same set of patient results; therefore, only the most recent one was included.…”
Section: Resultsmentioning
confidence: 99%
“…17,19,25 A rebound increase in ICP associated with rewarming was reported in 3 of the short-term cooling studies; 17,25,26 however, this adverse event was not reported in any of the long-term cooling studies. No difference in the development of pneumonia between control and hypothermia groups was reported in 5 trials, [26][27][28]32 and sepsis or pneumonia were more commonly reported in hypothermic patients in 2 trials. 17,31 No study reported an increase in hemorrhagic complications with hypothermia (either intracranial or systemic), though 4 reported thrombocytopenia 19,27,31,33 and 3 reported slight prolongations in the partial thromboplastin time or prothrombin time.…”
Section: Prophylactic Hypothermia For Traumatic Brain Injurymentioning
confidence: 96%
“…A higher rate of infection and worsening of coagulation have been reported in some clinical studies of hypothermia in neurotrauma [158], [159] and [160]. These complications, however, have not constituted a major problem in the majority of randomized studies [19], [20], [24] and [161], have been absent so far in ALF patients [80], [81], [119] and [120] and, importantly, they can be prevented and managed. New therapies, such as recombinant factor VIIa [162] or granulocyte colony-stimulating factor [163] could also be helpful.…”
Section: Therapeutic Implicationsmentioning
confidence: 98%
“…All observed decreases in ICP during cooling. Thirteen of these studies reported significant improvements in outcome associated with hypothermia [10,12-14,16,17,19-25]. All of these were performed in specialised neurotrauma centres, with experience in applying hypothermia and managing its side effects.…”
Section: Introductionmentioning
confidence: 99%
“…All of these were performed in specialised neurotrauma centres, with experience in applying hypothermia and managing its side effects. Ten were single centre studies [10,12,14,16,17,20,22-25], three (all performed in China) [14,20,22] were multi-centre. Four additional studies [11,15,18,21] observed a trend to improved outcome, but these differences were not statistically significant.…”
Section: Introductionmentioning
confidence: 99%